Long-term performance of an external stent for saphenous vein grafts: the VEST IV trial - Taggart, DP; Webb, CM; Desouza, A; Yadav, R; Channon, KM; De Robertis, F; Di Mario, C (BioMed Central, 2018)
Background Externally stenting saphenous vein grafts reduces intimal hyperplasia, improves lumen uniformity and reduces oscillatory shear stress 1 year following surgery. The present study is the first to present the longer-term (4.5 years) performance and biomechanical effects of externally stented saphenous vein grafts. Methods Thirty patients previously implanted with the VEST external stent in the randomized, within-patient-controlled VEST I study were followed up for adverse events; 21 of these were available to undergo coronary angiography and intravascular ultrasound. Results Twenty-one stented and 29 nonstented saphenous vein grafts were evaluated by angiography and ultrasound at 4.5 ± 0.3 years. Vein graft failure rates were comparable between stented and nonstented grafts (30 and 23% respectively; p = 0.42). All failures were apparent at 1 year except for one additional nonstented failure at 4.5 years. In patent vein grafts, Fitzgibbon perfect patency remained significantly higher in the stented versus nonstented vein grafts (81 and 48% respectively, p = 0.002), while intimal hyperplasia area (4.27 mm2 ± 1.27 mm2 and 5.23 mm2 ± 1.83 mm2 respectively, p≺ 0.001) and thickness (0.36 mm ± 0.09 mm and 0.42 mm ± 0.11 mm respectively, p ≺ 0.001) were significantly reduced. Intimal hyperplasia proliferation correlated with lumen uniformity and with the distance between the stent and the lumen (p = 0.04 and p ≺ 0.001 respectively). Conclusion External stenting mitigates saphenous vein graft remodeling and significantly reduces diffuse intimal hyperplasia and the development of lumen irregularities 4.5 years after coronary artery bypass surgery. Close conformity of the stent to the vessel wall appears to be an important factor.